2016
DOI: 10.3390/jrfm9020006
|View full text |Cite
|
Sign up to set email alerts
|

Down-Side Risk Metrics as Portfolio Diversification Strategies across the Global Financial Crisis

Abstract: Abstract:This paper features an analysis of the effectiveness of a range of portfolio diversification strategies, with a focus on down-side risk metrics, as a portfolio diversification strategy in a European market context. We apply these measures to a set of daily arithmetically-compounded returns, in U.S. dollar terms, on a set of ten market indices representing the major European markets for a nine-year period from the beginning of 2005 to the end of 2013. The sample period, which incorporates the periods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…All in all, the results of our analysis are not consistent with those presented in and Allen et al (2014A); although these are in line with those of Kirby and Ostdiek (2012) and Allen et al (2014b) for the hedge fund indices. Thus, although as in all empirical works the results obtained have to be taken with some degree of caution (since they are refered to a particular index over a certain time period), our findings lead us to infer that the naive strategy of 1/N can provide a good results during some episodes, being always exceeded by several portfolio optimization models.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…All in all, the results of our analysis are not consistent with those presented in and Allen et al (2014A); although these are in line with those of Kirby and Ostdiek (2012) and Allen et al (2014b) for the hedge fund indices. Thus, although as in all empirical works the results obtained have to be taken with some degree of caution (since they are refered to a particular index over a certain time period), our findings lead us to infer that the naive strategy of 1/N can provide a good results during some episodes, being always exceeded by several portfolio optimization models.…”
Section: Discussionsupporting
confidence: 49%
“…The 1/N strategy has proved as a difficult alternative to beat, demonstrating the practical difficulties to obtain an efficient portfolio And Allen et al, 2014a.). Therefore, we propose an efficiency analysis of the various methodologies compared with the naive diversification of 1/N and the main Spanish stock index, Ibex 35.…”
Section: Compared the Cvar And Conditionalmentioning
confidence: 99%
“…However, Basel Accord outlined three methods for computing the minimum capital charge for operational risk in a series of rising sophistication and risk sensitivity. Allen et al (2016) this study aimed to analyze the range effectiveness of portfolio diversification strategies, concentrating on down-side risk metrics, as a portfolio diversification strategy in a European market context. Thus, the results suggested that none of the more sophisticated optimization strategies appear to dominate naive diversification.…”
Section: Operational Risk Identification and Measurementmentioning
confidence: 99%
“…On the other hand, [34] develop a new VaR model based on financial markets overnight information. The ES is also used as risk measure for portfolio diversification strategy purposes [35] and for hedging purposes [36]. In any case, the use of ES poses a challenge to portfolio and risk managers because it is not clear which validation method the regulator and the industry should employ to test the proposed risk measure, that is, it is not clear how to evaluate the goodness of the ES risk measure.…”
Section: Literature Reviewmentioning
confidence: 99%